Extractability Effectiveness on Software Product Line - Mohammad Ali Torkamani (Institute of Advanced Engineering and Science, 2014)
A software product line consists of a family of software systems. Most of quality attributes are defined for single systems. When we are facing a family of products instead of a single system, some aspects of architecture evaluation, such as cost, time, and reusability of available assets, become more highlighted. In this paper a new quality attribute for software product line, which we called it extractability, is introduced. Also extractability measuring method and relationship between extractability with some quality attributes is presented. At the end, Extractability Effectiveness on Software Product Line is evaluated in practice.DOI:http://dx.doi.org/10.11591/ijece.v4i1.4106